Cardiac Autonomic and Blood Pressure Responses to an Acute Foam Rolling Session. Issue 10 (October 2018) - Lastova, Kevin; Nordvall, Michael; Walters-Edwards, Michelle; Allnutt, Amy; Wong, Alexei
Abstract : Abstract: Lastova, K, Nordvall, M, Walters-Edwards, M, Allnutt, A, and Wong, A. Cardiac autonomic and blood pressure responses to an acute foam rolling session. J Strength Cond Res 32(10): 2825–2830, 2018—Foam rolling (FR) is a self-myofascial release method that has become extremely popular among athletes and fitness enthusiasts for its ability to improve flexibility and range of motion and alleviate delayed-onset muscle soreness. However, the cardiac autonomic modulation and blood pressure (BP) responses induced by an acute FR session are currently unknown. This study evaluated the effects of an acute session of FR exercise on heart rate variability (HRV) and BP responses in healthy individuals. Fifteen (M = 8, F = 7) healthy subjects completed either an FR or nonexercise control trial in randomized order. Heart rate variability and BP measurements were collected at baseline, 10, and 30 minutes after each trial. There were significant increases ( p < 0.01) in markers of vagal tone (normalized high frequency) for 30 minutes after the FR trial, whereas no changes from baseline were observed after control. There were also significant decreases ( p < 0.05) in markers of sympathetic activity (normalized low frequency), sympathovagal balance (ratio of normalized low frequency to normalized high frequency), systolic BP, and diastolic BP at 10 and 30 minutes after the trial KB trial, whereas no changes from baseline were observed after the control trial. Our findings indicate that FR decreases sympathovagal balance for 30 minutes postintervention, which is concurrent with an important hypotensive effect. Further research is warranted to evaluate the potential cardiovascular protective effects of FR in diverse populations.